Metodologi SRA dan Ring Structure dalam Konsep Keteraturan Al-Qur’an menurut Michel Cuypers dan Raymond Farrin - Anas Miftah (AL-Ikhtiar : Jurnal Studi Islam, 2025)
The study of the orderliness of the Qur'an has long been a debate in the treasury of scholarship, especially among orientalists who consider the Qur'anic text to lack structural coherence. This study analyzes the Semitic Rhetorical Analysis (SRA) approach developed by Michel Cuypers and the Ring Structure theory proposed by Raymond Farrin as alternative methodologies to reveal the orderliness and harmony of the Qur'an. This study uses a library method by examining the primary works of Cuypers and Farrin as well as secondary literature related to the rhetorical analysis and structure of the Qur'an. The results of the study show that SRA emphasizes the existence of parallel, concentric, and mirror symmetrical patterns in verses and suras that form cohesion of meaning, while the Ring Structure theory displays a circular pattern in which the beginning and end of the text function as frames that emphasize the central message. Analysis of certain suras shows that parallel, chiastic, and ring order are not mere coincidences, but part of a deliberate rhetorical design. These findings not only refute orientalist criticisms of the Quran's irregularity but also open up new opportunities for interdisciplinary studies, including theology, literature, and linguistics. Thus, the integration of SRA and Ring Structure significantly contributes to enriching our understanding of the Quran's coherence, systematics, and universal relevance in the contemporary era. Abstrak Kajian tentang keteraturan Al-Qur’an telah lama menjadi perdebatan dalam khazanah kesarjanaan, terutama di kalangan orientalis yang menilai teks Al-Qur’an tidak memiliki koherensi struktural. Penelitian ini menganalisis pendekatan Semitic Rhetorical Analysis (SRA) yang dikembangkan Michel Cuypers dan teori Ring Structure yang dikemukakan Raymond Farrin sebagai metodologi alternatif untuk mengungkap keteraturan dan keselarasan Al-Qur’an. Penelitian ini menggunakan metode kepustakaan dengan menelaah karya-karya primer Cuypers dan Farrin serta literatur sekunder terkait analisis retorika dan struktur Al-Qur’an. Hasil kajian menunjukkan bahwa SRA menegaskan adanya pola simetris paralel, konsentris, dan cermin dalam ayat maupun surah yang membentuk kohesi makna, sedangkan teori Ring Structure menampilkan pola melingkar di mana bagian awal dan akhir teks berfungsi sebagai bingkai yang menegaskan pesan sentral. Analisis terhadap surah tertentu memperlihatkan bahwa keteraturan paralel, chiastic, dan cincin bukan sekadar kebetulan, melainkan bagian dari desain retoris yang disengaja. Temuan ini tidak hanya membantah kritik orientalis tentang ketidakteraturan Al-Qur’an, tetapi juga membuka ruang baru bagi studi lintas disiplin, baik dalam teologi, sastra, maupun linguistik. Dengan demikian, integrasi SRA dan Ring Structure memberikan kontribusi signifikan dalam memperkaya pemahaman tentang koherensi, sistematika, dan relevansi universal Al-Qur’an di era kontemporer.